(untitled) (The Research of Medical Science Review, 2024)
OBJECTIVE To determine the outcome of extracorporeal shock wave lithotripsy (ESWL) for bladder stones less than 2cm in size. METHODOLOGY The study was conducted in the Department of Urology at the Sindh Institute of Urology and Transplantation (SIUT) Karachi. A non-probability consecutive sampling technique was used to enroll the sample of 113 patients between 20 and 70 years of age, either gender, with single renal stones less than 2 cm in size. ESWL was performed by using a Storz Modulith Electromagnetic lithotripter (Karl Storz Lithotripsy-America Inc, Atlanta, GA), with stones localized by ultrasound and fluoroscopy. Treatment involved administering 200 shock waves at energy levels 2–3 per minute, followed by 3000 shocks at levels 4–6 at a rate of 70–90 per minute. Patients were advised to maintain adequate oral fluid intake and were followed up at two weeks, four weeks, and finally at eight weeks to assess the efficacy. The SPSS version 26.0 was used to evaluate the data. RESULTS The mean ± standard deviation of the sample of 113 patients was noted as 40.71 ± 10.78 years. Among them 69.9% were male while 30.1% were female. The average stone size was 8.85 ± 3.14 mm, the stone size between 4 to 9 mm represented 73.5% of patients and > 9 mm represented 26.5% of patients. The stone clearance was achieved in 69.9% patients while 30.1% had residual stones. Patients with a skin-to-stone distance of 70–125 mm had a significantly higher clearance rate of 74.7% compared to 50.0% in those with a skin-to-stone distance >125 mm (OR: 2.957, p = 0.023). CONCLUSION It is concluded that ESWL) is a safe and efficient treatment modality for bladder stones smaller than 2 cm. Successful stone clearance was independently predicted by BMI, skin-to-stone distance and the ESWL score. Outcomes were not significantly affected by age, stone size, gender or stone location. These results highlight the need to individualize patient factors for optimal ESWL outcomes.